2014
DOI: 10.4025/reveducfis.v25i2.21193
|View full text |Cite
|
Sign up to set email alerts
|

O nível de estresse de atletas de basquetebol em diferentes momentos do jogo em uma competição oficial

Abstract: RESUMOEste estudo teve como objetivo comparar indicadores psicofisiológicos do estresse entre atletas de basquetebol em competição. Participaram 38 atletas, durante as semifinais e finais de jogos estaduais. Foi aplicada a Escala de Humor de Brunel (BRUMS), antes e após os jogos como também foram colhidas amostras salivares dos atletas nas situações repouso, antes e após os jogos das semifinais e finais da competição. Para comparar os momentos pré e pós-jogos dos atletas e para as variáveis psicológicas (BRUMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Athletes showed low levels of cognitive anxiety and somatic anxiety. Although this was not a consistent finding in the literature, some studies [ 33 , 34 ] indicated that athletes do not have high anxiety scores. It is noteworthy that data collection in this study was performed after training sessions, which may have contributed to the low levels obtained.…”
Section: Discussionmentioning
confidence: 69%
“…Athletes showed low levels of cognitive anxiety and somatic anxiety. Although this was not a consistent finding in the literature, some studies [ 33 , 34 ] indicated that athletes do not have high anxiety scores. It is noteworthy that data collection in this study was performed after training sessions, which may have contributed to the low levels obtained.…”
Section: Discussionmentioning
confidence: 69%